T-bet Expression by Foxp3+ T Regulatory Cells is Not Essential for Their Suppressive Function in CNS Autoimmune Disease or Colitis - McPherson, Rhoanne C.; Turner, Darryl G.; Mair, Iris; O’Connor, Richard A.; Anderton, Stephen M. (Frontiers in Immunology, 2015)
Accumulation of T regulatory (Treg) cells within the central nervous system (CNS) during experimental autoimmune encephalomyelitis (EAE) is essential for the resolution of disease. CNS Treg cells have been shown to uniformly express the Th1-associated molecules T-bet and CXCR3. Here we report that the expression of T-bet is not required for the function of these Treg within the CNS. Using mice that lacked T-bet expression specifically within the Treg compartment, we demonstrate that there was no deficit in Treg recruitment into the CNS during EAE and no difference in the resolution of disease compared to control mice. T-bet deficiency did not impact on the in vitro suppressive capacity of Treg. Transfer of T-bet-deficient Treg was able to suppress clinical signs of either EAE, or colitis. These observations demonstrate that, although Treg can acquire characteristics associated with pathogenic Teff cells, this process is not necessarily required for their suppressive capacity and the resolution of autoimmune inflammation.